Soft tissue management around dental implant in esthetic zone - the current concepts and novel techniques - Teresa Chanting Sun; Tsung-Kai Chang (Elsevier, 2024)
It has been said, 'Bone sets the tone, but tissue is the issue.' In the field of implantology, while significant breakthroughs have been achieved in hard tissue regeneration, clinicians find it more challenging to handle soft tissue complications around dental implants. Successfully managing soft tissue around dental implants requires clinicians to have comprehensive knowledge of proper implant placement, prosthetic design and tissue management, and a high level of surgical skills for soft tissue augmentation and grafting. Autogenous gingival grafts can be utilized in various clinical situations, providing surgeons with great potential and freedom to enhance the quality and quantity of peri-implant soft tissue. Emerging trends, such as digital tools for treatment planning, minimally invasive surgical approaches, and innovative biomaterials, can also contribute to a more pleasing outcome. By elucidating these multifaceted considerations, this review will serve as a valuable resource for clinicians aiming to achieve functional and aesthetic excellence in implant-based oral rehabilitation.